Risk factors of mortality in nine years of follow-up after dynamic cardiomyoplasty Fatores determinantes de mortalidade em nove anos de seguimento pós cardiomioplastia dinâmica - Anderson Benício; Luiz Felipe P. Moreira; Fernando Bacal; Noedir A.G. Stolf; Sérgio A. Oliveira (Brazilian Journal of Cardiovascular Surgery, 2003)
PURPOSE: To retrospectively evaluate the survival rate of patients that underwent dynamic cardiomyoplasty, determining the influence of pre-, intra- and post-operative factors and the evolution of left ventricle ejection fraction according to the stimulation mode. METHOD: Forty-three patients that underwent dynamic cardiomyoplasty between May 1988 and September 1997 were analyzed. Functional class III was predominant (81.4%). The mean left ventricle ejection fraction was 19.37 ± 3.48%. Hospital death was 2.2% and 39 patients who completed the conditioning period had a mean follow up of 46 ± 26 months. Twenty-eight patients were predominantly maintained under stimulation mode 1:1 and 11 under 1:2 stimulation mode. RESULTS: Survival rate at nine years of follow up was 9%. The causes of death were progression of the heart failure and sudden cardiac death. Functional class, the pulmonary vascular-resistance index and stimulation mode were identified as risk factors. The maintenance of the increase of the left ventricle ejection fraction when compared to the preoperative values was more consistent during the studied period when the graft was stimulated in the 1:2 mode. CONCLUSION: Late results of dynamic cardiomyoplasty are limited by the high incidence of deaths by progression of the heart failure and sudden cardiac death. Survival rate is influenced by the preoperative clinical condition and by the stimulation mode. Muscle graft performance is higher at late follow up with the 1:2 stimulation mode. OBJETIVO: Analisar, retrospectivamente, a sobrevivência dos pacientes submetidos a cardiomioplastia dinâmica, determinando a influência de fatores pré, intra e pós-operatório e o comportamento da fração de ejeção conforme o modo de estimulação. MÉTODO: Foram analisados 43 pacientes submetidos a cardiomioplastia dinâmica, no período de maio de 1988 a setembro de 1997. A classe funcional III foi predominante (81,4%). A fração de ejeção média do VE foi de 19,37±3,48%. A mortalidade hospitalar foi de 2,2% e 39 pacientes, que completaram o período de condicionamento, tiveram seguimento médio de 46±26 meses. Vinte e oito pacientes foram mantidos predominantemente sob estimulação em modo 1:1 e 11 pacientes foram mantidos predominantemente sob estimulação em modo 1:2. RESULTADOS: A sobrevivência foi de 9% em nove anos. As causas de óbito foram progressão da insuficiência cardíaca e morte súbita. A classe funcional, o índice de resistência vascular pulmonar e o modo de estimulação foram identificados como fatores independentes de prognóstico. A manutenção da melhora da fração de ejeção do VE em relação ao pré-operatório foi mais consistente ao longo do período estudado, quando o enxerto muscular foi estimulado em modo 1:2. CONCLUSÃO: Os resultados tardios da cardiomioplastia dinâmica são limitados pela alta incidência de morte súbita e de óbitos decorrentes da progressão da doença de base. A sobrevivência é influenciada pela condição clínica pré-operatória e pelo modo de estimulação do enxerto. O desempenho do enxerto muscular é mais satisfatório a longo prazo quando submetido à estimulação modo 1:2.